Analisis Pengaruh Media Sosial dan Motivasi terhadap Kinerja Dosen Universitas Swasta di Kota Jambi pada Era Digital Modernisasi - Yamali, Fakhrul Rozi; Yusiana, Venny; Adisetiawan, R.; Putri, Ririn Noviyanti (Universitas Batanghari Jambi, 2025)
The purpose of this study is to analyze the influence of social media and motivation on the performance of private university lecturers in Jambi City. This study is a quantitative study with an observational analytical method with a design in this study in the form of a cross-sectional study approach. Respondents in this study were some of the lecturers at Jambi Private University, totaling 240 people. The results of this study indicate that simultaneously and partially there is a positive and significant influence between the variables of social media and motivation on the performance of private university lecturers in Jambi City.